Five Dinuclear Lanthanide Complexes Based on 2,4-dimethylbenzoic Acid and 5,5′-dimethy-2,2′-bipyridine: Crystal Structures, Thermal Behaviour and Luminescent Property - Zhao, Jia-Yuan; Ren, Ning; Zhang, Ying-Ying; Tang, Kun; Zhang, Jian-Jun (Frontiers in Chemistry, 2021)
A series of new complexes, [Ln(2,4-DMBA)3(5,5′-DM-2,2′-bipy)]2 (Ln=Sm(1), Eu(2)), [Pr(2,4-DMBA)3(5,5′-DM-2,2′-bipy)]2•0.5(C2H5OH) (3), [Ln(2,4-DMBA)3(5,5′-DM-2,2′-bipy)]2•0.5(2,4-DMBAH)•0.25(5,5′-DM-2,2′-bipy) (Ln=Tb(4), Dy(5)) (2,4-DMBA = 2,4-dimethylbenzoate, 5,5′-DM-2,2′-bipy = 5,5′-dimethy-2,2′-bipyridine) were synthesized via hydrothermal reaction conditions. The complexes were characterized through elemental analysis, Infrared spectra (IR), Raman (R) spectra, UV-Vis spectra, single X-ray diffraction. Single crystal data show that complexes 1-5 are binuclear complexes, but they can be divided into three different crystal structures. The thermal decomposition mechanism of complexes 1-5 were investigated by the technology of simultaneous TG/DSC-FTIR. What's more, the luminescent properties of complexes 1-2 and 4 were discussed, and the luminescence lifetime (τ) of complexes 2 and 4 were calculated.